A double-negative feedback loop between DEAD-box protein DDX21 and Snail regulates epithelial-mesenchymal transition and metastasis in breast cancer. (28th November 2018) - Zhang, Hao; Zhang, Yanqiu; Chen, Chen; Zhu, Xiaoyun; Zhang, Chao; Xia, Yuanzheng; Zhao, Yucheng; Andrisani, Ourania M.; Kong, Lingyi
Abstract: DDX21, a DEAD-box protein, implicated in fundamental aspects of RNA metabolism such as gene transcription. DDX21 expression is dysregulated in cancer, but its specific contribution to tumor invasion and metastasis remains to be determined. Here, we demonstrate DDX21 down-regulation is associated with highly metastatic and poor prognosis human breast cancers. DDX21 overexpression inhibited, while DDX21 knockdown promoted epithelial-mesenchymal transition (EMT) in vitro and in vivo. Overexpression of Snail reversed DDX21 mediated inhibition of cell invasion. On the other hand, independent of its helicase activity, DDX21 suppressed Snail transcription by recruiting SUZ12 and EZH2, two core subunits of PRC2 (polycomb-repressive complex 2), to the Snail promoter. Furthermore, down-regulation of DDX21 is mediated by miR-218–5p. Surprisingly, Snail also modulates DDX21 transcription. Snail overexpression decreased DDX21 transcription, whereas Snail knockdown increased DDX21 expression. These novel observations demonstrate firstly, the antagonism/double negative feedback loop between DDX21 and Snail transcription, and secondly, the crucial role of miR-218–5p in promoting EMT, acting by decreasing the ratio of DDX21/Snail. Our results identify DDX21 as a breast cancer metastasis suppressor; blocking miR-218–5p will stabilize DDX21 and epigenetically suppress Snail expression and EMT. Highlights: Low DDX21 expression correlates with decreased E-cadherin expression and poor clinical outcomes of breast cancer patients. DDX21 suppresses Snail transcription by recruiting EZH2 and SUZ12. DDX21 and Snail form a double-negative feedback loop. MiR-218–5p targets DDX21 and promotes cell migration and invasion.